PENGARUH KEPUASAN KERJA DAN PROMOSI JABATAN TERHADAP KOMITMEN ORGANISASI KARYAWAN PT. BANK PERKREDITAN RAKYAT (BPR) BATURAJA: the influence of job satisfaction and promotion on the organizational commitment of employees of PT. Bank Perkreditan Rakyat (BPR) Baturaja (Ekonomika, 2023)
This study aimed to determine the influence of job satisfaction and promotion onthe organizational commitment of employees of PT. Bank Perkreditan Rakyat(BPR) Baturaja. The data collection technique used in this research was throughthe distribution of questionnaires. The population was 39 permanent employees.The data analysis technique used was Multiple Linear Regression using SPSS 26.Based on the partial analysis results, there was an influence of job satisfaction onthe organizational commitment of employees of PT. Bank Perkreditan Rakyat(BPR) Baturaja with t-count value (3,235)> t-table (2,028). The promotionvariable had an influence on the organizational commitment of employees of PT.Bank Perkreditan Rakyat (BPR) Baturaja with t-count value 3,622> t-table(2,028). Simultaneously, it was found that there was an influence of jobsatisfaction and promotion on the organizational commitment of employees of PT.Bank Perkreditan Rakyat (BPR) Baturaja with F-count value (18,32)> F-table(3,26). The coefficient of determination (R2) obtained was 0.504. This showed thecontribution of the influence of job satisfaction and promotion on organizationalcommitment was 50.4%, while the remaining 49.6% was influenced by othervariables outside of this research, namely openness culture, organizationaldirection, and work rewards that met needs (Rosa et al., 2022:305).